2011
DOI: 10.1093/ajae/aaq155
|View full text |Cite
|
Sign up to set email alerts
|

Habit Formation and Demand for Sugar‐Sweetened Beverages

Abstract: Using scanner data, we estimated demand for nine nonalcoholic beverages under habit formation. We found strong evidence for habit formation. Although demand for sugar-sweetened beverages by lowincome households is less elastic to own-price changes compared with high-income households, there is evidence that high-income households consider beverages to be more substitutable than low-income households do. A half-cent per ounce tax on store-purchased sugar-sweetened beverages will result in a moderate reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
158
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(168 citation statements)
references
References 45 publications
4
158
0
Order By: Relevance
“…Many studies have dealt with the implications of taxes on energy dense snack foods and soft drinks [62,[65][66][67]. In the US, there are about 19 states that levy taxes on soft drinks, candy, chewing gum, or snack foods (potato chips, pretzels, and others) [62].…”
Section: Obesity: a Results Of Market Failure?mentioning
confidence: 99%
“…Many studies have dealt with the implications of taxes on energy dense snack foods and soft drinks [62,[65][66][67]. In the US, there are about 19 states that levy taxes on soft drinks, candy, chewing gum, or snack foods (potato chips, pretzels, and others) [62].…”
Section: Obesity: a Results Of Market Failure?mentioning
confidence: 99%
“…Higher-income individuals would pay $18.84. Another similar study found a SSB tax to be similarly regressive but, again, of small magnitude (28). Because low income individuals are projected to lose slightly more weight from a SSB tax than higher income individuals, this income burden may be more than abated by health improvements.…”
mentioning
confidence: 93%
“…Much evidence demonstrates the effect, or likely effect, of taxes on SSB consumption (3,(22)(23)(24)(25)(26)(27)(28)(29). Several studies, most focused on soda/soft drinks, have documented associations between higher SSB prices and lower consumption.…”
mentioning
confidence: 99%
See 2 more Smart Citations